(untitled) (The International Journal for Scientific Research, 2023)
What is not disputed is that language is the most prominent means of communication between different linguistic groups. Since all linguistic groups meet in the element of language, and among those languages is the Arabic language, which has a communicative system that makes it maintain an important place among the languages of the world, it is replete with its vocabulary that is truly capable of encompassing new and old meanings, and the Holy Qur’an has attested to this; By becoming aware of the vocabulary of the words of the Lord of the Worlds. Computational linguistics emerged as a result of the boom in computer science and artificial intelligence research that was primarily aimed at imitating and simulating the motor and mental processes practiced by advanced organisms such as humans. This ambiguity referred to has been termed in Arabic as ambiguity, and it is matched by the clear meaning that cannot be read beyond any interpretation, and it is the safest of ambiguity. This is what I present in this paper through investigation and understanding in this regard.